Factors Influencing Postoperative Recurrence and Live Birth Achievement after Laparoscopic Surgery for Ovarian Endometrioma: A Retrospective Study in a Regional Core Hospital - Ryosuke Arakaki; Wataru Isono; Hiroaki Fukuda; Junya Tanaka; Arisa Minamino; Shiko Hayashi (Clinical and Experimental Obstetrics & Gynecology)
Background: Ovarian endometrioma (OMA) is a common gynecological condition affecting women of reproductive age, often requiring laparoscopic surgery for removal. However, the management of OMA, including postoperative hormone therapy, is complex and must be tailored to the individual's conditions. Therefore, to provide meaningful insights, we aimed to analyze 10 years of accumulated data from patients who underwent laparoscopic surgery for OMA, with a primary focus mainly on postoperative OMA recurrence and live birth outcomes. Methods: We reviewed the medical records of 158 patients who underwent laparoscopic surgery for OMA, including total laparoscopic cystectomy (TLC) (79 patients), total laparoscopic adnexectomy (TLA) (62 patients), or both unilateral TLA and contralateral TLC (17 patients), between January 2014 and December 2023. Among the OMA patients, we identified 7 cases of postoperative OMA recurrence out of 158 patients, and 23 live births among 79 TLC patients. We performed a multivariate logistic regression analysis to assess the impact of each representative factor on postoperative OMA recurrence and live birth achievement. Results: The multivariate analyses of the 158 patients revealed that advance age and massive blood loss were significantly associated with an increased risk of postoperative OMA recurrence, while postoperative hormone treatment was associated with a decreased risk of recurrence. In the analysis of live birth achievement among the 79 TLC patients, advanced age, postoperative hormone treatment and cancer antigen 125 (CA125) positivity were significantly associated with a reduced likelihood of achieving live birth. Conclusions: Our data highlight the unfavorable effects of advanced age, massive blood loss and CA125 positivity on the outcomes of laparoscopic surgery for OMA. Additionally, postoperative hormone treatment was found to decrease postoperative OMA recurrence. These findings may offer more accurate information to guidance in selecting treatment options for patients with OMA.